The Roles of Picornavirus Untranslated Regions in Infection and Innate Immunity - Kloc, Anna; Rai, Devendra K.; Rieder, Elizabeth (Frontiers in Microbiology, 2018)
Viral genomes have evolved to maximize their potential of overcoming host defense mechanisms and to induce a variety of disease syndromes. Structurally, a genome of a virus consists of coding and noncoding regions, and both have been shown to contribute to initiation and progression of disease. Accumulated work in picornaviruses has stressed out the importance of the noncoding RNAs, or untranslated 5′- and 3′-regions (UTRs), in both replication and translation of viral genomes. Unsurprisingly, defects in these processes have been reported to cause viral attenuation and affect viral pathogenicity. However, substantial evidence suggests that these untranslated RNAs may influence the outcome of the host innate immune response. This review discusses the involvement of 5′- and 3′-terminus UTRs in induction and regulation of host immunity and its consequences for viral life cycle and virulence.